AKIBAT HUKUM TERJADINYA FORCE MAJEURE DALAM PERJANJIAN PENGANGKUTAN BARANG (STUDI KASUS J&T EXPRESS DI KABUPATEN SINTANG) - JESSICA PUTRI IBANI NIM. A1011171214 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Force majeure in the Civil Code only explains that force majeure results in the debtor being released from demands for compensation. The absence of a specific understanding of force majeure regulated in legislation has given rise to many interpretations and opinions by legal experts regarding the meaning of force majeure, even for the parties to the agreement. This often triggers disputes in an agreement that experiences force majeure.Like the flood that occurred in Sintang Regency in 2021, to be precise in early November, where the flood submerged 12 sub-districts in Sintang for four weeks which caused delays or even stopped various community activities. One of them is the activity of transporting goods carried out by carrier services, this activity is greatly disrupted during floods because the floods that occur close access roads which are important means of shipping goods.Starting from the descriptions in the research background, the problem in this research is: